A parametric study of the mooring system design parameters to reduce wake losses in a floating wind farm. Issue 4 (1st May 2022) - Youssef Mahfouz, Mohammad; Hall, Matthew; Cheng, Po Wen
Abstract: Wake effects inside a conventional fixed bottom wind farm decrease the power produced by the downwind turbines, hence decreasing the farm's annual energy production (AEP). However, floating offshore wind turbines (FOWTs) have the ability to relocate their positions laterally through surge and sway motions. This flexibility provides a new degree of freedom (DOF) in the floating wind farm layout, which can be used to decrease the aerodynamic interactions inside the floating wind farm and hence decrease the wake losses. The lateral movement of FOWTs can be passively controlled by the mooring system design. The mooring system's restoring characteristics allows the FOWT to only move within a specific area in the x-y plane known as the watch circle. Current state of the art mooring system designs are following oil and gas design basis where the floating platforms are not allowed to have large lateral displacements. In this work, we use full factorial design to analyse the effect of different mooring system design parameters on the ability of the floater to relocate its position. The analysis shows that each design parameter has a different way of affecting the FOWT's response. The mooring lines' headings control which wind directions cause the biggest displacements in the crosswind direction. The smaller the lines' diameters the higher the displacements of the FOWT. Finally, the longer the line length the smaller the mooring system's stiffness and hence the larger the FOWT's displacement. The results of this study can be used as the basis for floating wind farm optimization, in which the wind turbines are allowed to passively relocate their positions according to the wind speed and wind direction.